PlmA, a New Member of the GntR Family, Has Plasmid Maintenance Functions in Anabaena sp. Strain PCC 7120 - Lee, Martin H. (American Society for Microbiology, 2003)
The filamentous cyanobacterium Anabaena (Nostoc) sp. strain PCC 7120 maintains a genome that is divided into a 6.4-Mb chromosome, three large plasmids of more that 100 kb, two medium-sized plasmids of 55 and 40 kb, and a 5.5-kb plasmid. Plasmid copy number can be dynamic in some cyanobacterial species, and the genes that regulate this process have not been characterized. Here we show that mutations in an open reading frame, all1076, reduce the numbers of copies per chromosome of several plasmids. In a mutant strain, plasmids pCC7120δ and pCC7120ζ are both reduced to less than 50% of their wild-type levels. The exogenous pDU1-based plasmid pAM1691 is reduced to less than 25% of its wild-type level, and the plasmid is rapidly lost. The peptide encoded by all1076 shows similarity to members of the GntR family of transcriptional regulators. Phylogenetic analysis reveals a new domain topology within the GntR family. PlmA homologs, all coming from cyanobacterial species, form a new subfamily that is distinct from the previously identified subfamilies. The all1076 locus, named plmA, regulates plasmid maintenance functions in Anabaena sp. strain PCC 7120.